O uso de jogos e simulação computacional como instrumento de aprendizagem : campeonato de aviões de papel e o ensino de hidrodinâmica - Souza, Ericarla de Jesus (2015)
This work presents a proposal to jointly use educational games, experimental activities and computer simulations using the Modellus software in teaching as teaching-learning technique of physics content in general. The content addressed in this work is the hydrodynamics and its application in the physical concepts involved in flying aircraft. The survey was conducted with students of the second year of high school in two public schools. We use a didactic sequence using own teaching materials, whose material was guided by low-cost experiments. We use as a motivating theme a paper airplane championship held in two stages. In the first meeting within the school itself and the last meeting in a dispute between the two schools carried out in the UFS. The theoretical framework is based on the theory of mental models of John Laird and in the theory of meaningful learning of Ausubel, so that the evaluations of previous knowledge of the students were made through evaluation of test type questionnaire. Learning content is reinforced through the use of computer simulation using the software Modellus. The students´ evaluation was made with the use of educational games: crosswords, word searches and games of the seven errors. The assessment was carried out by applying questions of the type alternative conceptions, which was applied at the beginning and end of each activity in the instructional sequence. The results were evaluated in qualitative and quantitative way, comparing student performance before and after the application of instructional sequence. The results indicate that the use of educational games, experimental activities and the software complement each other providing motivation to students, as well as, in most cases, meaningful learning and increased in interest in the subject of Physics.